Predictive value of neurophysiological monitoring during posterior communicating artery aneurysm clipping for postoperative neurological deficits - Tang, Fengjiao; Li, Shifang; Wang, Juntao; Tang, Wanzhong; Feng, Yugong (Frontiers in Surgery, 2023)
Objective: This study aimed to evaluate the diagnostic effect of intraoperative neurophysiological monitoring in identifying intraoperative ischemic events and predicting postoperative neurological dysfunction during PCoA aneurysm clipping, as well as to explore the safe duration of intraoperative temporary clipping of the parent artery. Methods: All 71 patients with PCoA aneurysm underwent craniotomy and aneurysm clipping. MEP and SSEP were used for monitoring during operation to evaluate the influence of MEP/SSEP changes on postoperative neurological function. Receiver operating characteristic (ROC) curve analysis was used to calculate optimal duration of intraoperative temporary clipping. RESULTS: Patients with intraoperative MEP/SSEP changes were more likely to develop short-term and long-term neurological deficits than those without MEP/SSEP changes (p < 0.05). From the ROC curve analysis, the safe time from the initiation of temporary clipping during the operation to the early warning of neurophysiological monitoring was 4.5 minutes (AUC = 0.735, 95%CI 0.5558-0.912). Taking 4.5 minutes as the dividing line, the incidence of short-term and long-term neurological dysfunction in patients with temporary clipping >4.5 minutes was significantly higher than that in patients with temporary clipping ≤4.5 minutes (P=0.015, P=0.018). Conclusion: Intraoperative MEP/SSEP changes are significantly associated with postoperative neurological dysfunction in patients with PCoA aneurysms. The optimal duration of temporary clipping of the parent artery during posterior communicating aneurysm clipping was 4.5 minutes under neurophysiological monitoring.